1992
DOI: 10.1042/bj2830829
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of echinoderm casein kinase II. Regulation by protein kinase C

Abstract: Casein kinase II (CKII) is one of several protein kinases that become activated before germinal-vesicle breakdown in maturing sea-star oocytes. Echinoderm CKII was purified over 11000-fold with a recovery of -10% by sequential fractionation of the oocyte cytosol on tyrosine-agarose, heparin-agarose, casein-agarose and MonoQ. The purified enzyme contained 45, 38 and 28 kDa polypeptides, which corresponded to its a, c' and , subunits respectively. The ,3-subunit was autophosphorylated on one major tryptic peptid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
1
1

Year Published

1992
1992
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 52 publications
3
30
1
1
Order By: Relevance
“…The CK I1 kinases themselves are substrates for phosphorylation by ~34'~'' (Litchfield et al, 1992) and protein kinase C (Sanghera et al, 1992). The M-phase-specific ~3 4 '~'~ protein kinase can phosphorylate the p subunit of CK I1 and increase its activity (Mulner-Lorillon et al, 1990), and when epidermal growth factor stimulates CK I1 activity, it apparently does so by stimulating an increase in its phosphorylation state (Ackerman et al, 1990).…”
mentioning
confidence: 99%
“…The CK I1 kinases themselves are substrates for phosphorylation by ~34'~'' (Litchfield et al, 1992) and protein kinase C (Sanghera et al, 1992). The M-phase-specific ~3 4 '~'~ protein kinase can phosphorylate the p subunit of CK I1 and increase its activity (Mulner-Lorillon et al, 1990), and when epidermal growth factor stimulates CK I1 activity, it apparently does so by stimulating an increase in its phosphorylation state (Ackerman et al, 1990).…”
mentioning
confidence: 99%
“…It has been suggested that CKII might have potentially important roles in neuronal function such as neuronal differentiation and proliferation (Blanquet, 2000). It was demonstrated that PKC stimulation via phorbol ester treatment increases CKII activity (Sanghera et al, 1992;Silva-Neto et al, 2002). PKC is also known to stimulate PLD activity (Frohman and Morris, 1999).…”
Section: Ckii Is Involved In Pma-induced Pld Activationmentioning
confidence: 99%
“…kinase mRNAs suggests that different isoforms may play tissue-specific roles. Thus MAP kinases have been implicated in the M phase of the meiotic cycle [6,8,9], in the G0-to-Gl progression of quiescent cells [7,8,10], and may play a role in the differentiation of PC-12 cells [50,51]. Human tissues are physiologically regulated by a variety of extracellular factors that may employ a diversity of signal transduetion pathways.…”
Section: ~mentioning
confidence: 99%
“…Members of this family of kinases have been implicated in a wide variety of cellular processes. MAP kinases are activated during the M phase of the meiotic cycle [6,8,9] and during mitogenic stimulation of quiescent cells [7,8,10]. It has been shown that MAP kinases can induce reorganization of microtubules in vitro [11], and also may modulate Myc- [12] and Jun-[I 3] mediated activation of eerie expression.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation